2017
DOI: 10.1159/000482001
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the Context of Medical Disorders: New Pharmacological Pathways Revisited

Abstract: The depressive state has been characterised as one of elevated inflammation, changed cardiovascular parameters and a deranged metabolic situation all of which holds promise for a better understanding and handling of treatment-resistance in affective disorders as well as for future developments in treatment algorithms. In this context several biomarkers are differentially regulated by antidepressant treatment and connected to metabolic, inflammatory, cardiovascular and apoptotic components of the pathophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 128 publications
(169 reference statements)
0
1
0
Order By: Relevance
“…The COX-2 selective inhibitor celecoxib inhibits prostaglandin and downstream cytokine production (Strekalova et al, 2022). Thus, several clinical studies have shown that celecoxib enhances the antidepressant effect; however, some studies have indicated that celecoxib might increase brain inflammation (Baune, 2017;Lang and Walter, 2017;Alboni et al, 2018;Strumila et al, 2022). These conflicting results may be resolved through more detailed basic and clinical studies in the future (Luning Prak et al, 2022).…”
Section: Nsaidsmentioning
confidence: 99%
“…The COX-2 selective inhibitor celecoxib inhibits prostaglandin and downstream cytokine production (Strekalova et al, 2022). Thus, several clinical studies have shown that celecoxib enhances the antidepressant effect; however, some studies have indicated that celecoxib might increase brain inflammation (Baune, 2017;Lang and Walter, 2017;Alboni et al, 2018;Strumila et al, 2022). These conflicting results may be resolved through more detailed basic and clinical studies in the future (Luning Prak et al, 2022).…”
Section: Nsaidsmentioning
confidence: 99%